Penerapan Asas-Asas Umum Pemerintahan Yang Baik Dalam Pemberhentian Tidak Dengan Hormat Terhadap Anggota Polri - Maulidin, Maulidin; Gani, Iskandar A.; Efendi, Efendi (Universitas Negeri Surabaya, 2023)
This study aims to analyze one form of government action is the imposition of Dishonorable Dismissal (PTDH) sanctions against members of the National Police. There are legal problems when in practice the imposition of PTDH sanctions against members of the Indonesian National Police within the Aceh Regional Police raises problems with their compliance with laws and regulations and the general principles of good governance (AUPB). This study uses a normative juridical method, with a statutory approach, a concept approach, and a case approach. This study also uses empirical juridical methods with a socio-legal approach. The results of the study confirm that the Sanctions of Dishonorable Dismissal (PTDH) against members of the Indonesian National Police by authorized officials have not implemented the General Principles of Good Governance (AUPB). This also includes several principles in good governance that have not been implemented including the principle of legal certainty, the principle of balance, the principle of accuracy, and the principle of impartiality.